Digitalization and Education Equity in Remote Areas: Challenges and Strategic Solutions - Muslimin, Muslimin; Indrawati, RA (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The COVID-19 pandemic has accelerated digitalization in the education sector, highlighting disparities in technology access, particularly in remote areas like Bone Regency, South Sulawesi. This study explores the impact of digitalization on equitable access to education in this region and identifies challenges and potential solutions to bridge the digital divide. The study used ethnographic methods to gather insights from selected students, teachers, academics, and parents. Findings reveal that limited digital infrastructure, lack of technology skills, and economic disparities are major barriers to digital education in Bone Regency. Social norms and gender roles further affect students' ability to use technology effectively, particularly for female students. Initiatives such as enhancing teacher training in digital skills, partnering with the private sector for infrastructure support, and implementing flexible hybrid learning models are identified as possible solutions. This study contributes to ongoing discussions about digital equity in education, providing actionable recommendations for policymakers to expand inclusive digital education access in remote areas.